Identification of Omega 3, EPA and DHA Content on Toddler Brain Development in Lamalera Village, Lembata Regency 2024 - Reginaldis Maristella Surung; Petrus Afendi (Syntax Corporation, 2026)
Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA) are omega-3 fatty acids. Omega-3, EPA, and DHA are essential fatty acids that cannot be produced naturally by the human body. These fatty acids are obtained from fish, nuts, and other foods or beverages containing omega-3 compounds. Whale oil contains EPA and DHA, which are important for the formation of brain cells and the improvement of cognitive development in toddlers. The purpose of this study was to determine the effect of omega-3 content in whale oil on the brain development of toddlers in Lamalera Village. Data collection was conducted through interviews with the community in Lamalera Village and experimental analysis by sending whale oil samples to LPPT UGM to determine the EPA and DHA content in whale oil. Data analysis was performed by combining qualitative and quantitative methods. The findings showed that the omega-3 content (EPA and DHA) may influence the brain development of toddlers, as demonstrated by laboratory tests indicating high levels of DHA fatty acids in whale oil. Based on the refractive index results, the whale oil was found to be relatively pure and had not been contaminated by various interfering substances. In addition, the whale oil exhibited high viscosity, as demonstrated by the viscosity test results, indicating its thick consistency. Based on these findings, whale oil appears to have a significant influence on the brain development of toddlers.